Caracterização do perfil psicomotor e rastreamento de ansiedade e depressão em crianças com transtorno do desenvolvimento da coordenação - Draghi, Tatiane Targino Gomes (2019)
Developmental Coordination Disorder (DCD) is a deficit in motor coordination that interferes with the child's functionality. Due to slowness and inaccuracy in motor skills such as running, jumping, writing and flinging, motor performance is compromised, becoming under that expected in relation to children with typical development. This difficulty makes children to isolate from games and friends, since they perceive their limitation, which can lead to psychological damages such as anxiety and depression. Based on this, considering the integrality of the child (biopsychosocial), the objective of this dissertation was to track and characterize the psychomotor profile of children with Developmental Coordination Disorder, which resulted in three articles. Study I, entitled 'Symptoms of Anxiety and Depression in Children with Developmental Coordination Disorder: A Systematic Review', aimed to find evidence in the literature of anxiety/depression symptoms in children with DCD compared to their pairs without DCD. The results show significant evidence on the relationship between DCD, anxiety and depression. Study II, entitled "Symptoms of anxiety and depression in schoolchildren with and without Developmental Coordination Disorder", whose objective was to identify whether reported symptoms of anxiety and depression are related to the presence of DCD in Brazilian school-aged children. The results indicate that Brazilian children have a high risk for anxiety, regardless of motor performance and age; however, children with DCD of 10-12 years of age report a significantly higher number of depressive symptomatology compared to their non-DCD pairs. Study III, entitled "Motor performance evaluation of Brazilian children with Developmental Coordination Disorder through the Movement Assessment Battery for Children and the Körperkoordinationstest Für Kinder", with the objective of comparing the motor performance of Brazilian children with moderate DCD and severe DCD in 7-8 and 9-10 years of age groups. As a result, in the evaluation of motor performance through MABC-2, the greatest deficit was observed in children with severe DCD, regardless of age, while in motor assessment performed by KTK this deficit remained significant only in children with severe DCD of 7- 8 years.